PENGEMBANGAN KARAKTER MAHASISWA BERBASIS PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI - Prasetya, Irwan; Riza Hadikusuma; Muhamad Reza Febrian; Angellia Malika Putri Setiawan (Politeknik Negeri Jakarta, 2024)
Higher education is not only aimed at transferring knowledge, but also at forming strong characters in students. Islamic religious education in higher education can be a strong foundation in developing students' characters. Good character is an important aspect in preparing students to face the challenges of life in the future, both professionally and personally. Therefore, research on the development of student character based on Islamic religious education is very relevant. This study aims to develop an effective Islamic Religious Education (PAI) model in building student character in higher education and to assess the effectiveness of the model in practice. In addition, this study also provides recommendations for the development of more effective Islamic religious education. The research methodology involves the development of an educational model based on Islamic religious principles through a participatory approach, followed by the implementation of the model in several higher education institutions. Data were collected through questionnaires, interviews with students and lecturers, and observations of PAI activities. The results of the study showed that the developed model succeeded in improving several aspects of student character, including integrity, responsibility, and empathy. Evaluation of the effectiveness of the model indicated a significant increase in student character development that was in line with Islamic values. Recommendations for further development include deeper integration of Islamic principles in the curriculum, training for lecturers, and ongoing evaluation to ensure the sustainability and effectiveness of the model. This research is expected to provide significant contributions to efforts to develop student character through Islamic religious education in higher education.